Teamwork competencies for interprofessional cancer care in multiteam systems: A narrative synthesis. Issue 4 (4th July 2022) - Chollette, Veronica; Doose, Michelle; Sanchez, Janeth; Weaver, Sallie J.
ABSTRACT: Numerous teamwork competency frameworks are designed for co-located, procedure-driven teams delivering care in acute settings. Little is known about their applicability or evaluation among larger teams-of-teams, known as multiteam systems (MTS), involved in delivering care for complex chronic conditions like cancer. In this review we aimed to identify studies examining teamwork competencies or teamwork competency frameworks developed or tested in healthcare teams, identify the extent to which they have been applied or evaluated in cancer care, and understand their applicability to larger MTSs involved in coordinating cancer care. We identified 107 relevant original articles, consensus statements, and prior systematic reviews published from 2013–2019. Most original papers ( n = 96) were intervention studies of inpatient acute care teams (52, 54%). Fifty-eight articles (60%) used existing frameworks to define competency domains. Four original articles and two consensus statements addressed teamwork competencies for cancer care. Few frameworks or interprofessional education (IPE) curricula specifically addressed teamwork among larger, distributed teams or examined competencies necessary to overcome care coordination challenges in cancer care MTSs. Research guiding the development of frameworks and IPE that consider challenges to effective coordination among larger MTSs and studies of their impact on patient and clinical outcomes is essential to optimal, high-quality care.